Volatility Spillover In Stock And Commodity Futures Market: Empirical Analysis In Indonesia’s Financial Market - Saadah, Siti (Jurnal Manajemen, 2018)
Volatility spillover between stock markets causes insignificancy of diversification. Therefore, other investment alternatives is required to build an optimal portfolio, one of them being commodity futures. The low correlation between commodity futures and stocks indicates the advantage of diversification in investment portfolio containing both assets. In order to prove the advantage of diversification, author tested the existence of volatility spillover during September 16, 2010 - September 30, 2015. Estimation result using GARCH method indicates the presence of significant volatility spillover from stock exchange to commodity futures exchange. An important implication of this finding is that if the sectoral stock index and commodity futures are incorporated into an investment portfolio, the investor will not have optimal diversification advantage. This is because there is a correlation between performance of both markets as a result of both markets having the same characteristics in response to the shock that is coming.